2011
DOI: 10.1111/j.2041-210x.2011.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of fatty acid–specific stable isotope analysis for trophic studies

Abstract: Summary1. Fatty acid-specific stable isotope analysis (FA-SIA) is expected to encompass most of the limits encountered when using more classical trophic markers such as bulk tissue stable isotope or fatty acid analyses. However, an essential premise for using FA-SIA for trophic studies is that the individual FA d 13C values of the consumer reflect those of its diet. Field studies using FA-SIA have so far made this assumption, which is not necessarily supported by the rare experimental tests. 2. A feeding exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 42 publications
5
91
0
Order By: Relevance
“…The first half of this parabolic tendency, namely the significant depletion of the essential 18:2n-6 and especially 18:3n-3 compared to their less saturated precursors, is in a good agreement with the ideas, that the kinetic isotope effect make more unsaturated fatty acids lighter, than their precursors [6], [9], [11]. In contrast, the other half of the found tendency (18:3n-3<18:4n-3<20:5n-3≈22:6n-3) evidently contradicts the above postulate.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The first half of this parabolic tendency, namely the significant depletion of the essential 18:2n-6 and especially 18:3n-3 compared to their less saturated precursors, is in a good agreement with the ideas, that the kinetic isotope effect make more unsaturated fatty acids lighter, than their precursors [6], [9], [11]. In contrast, the other half of the found tendency (18:3n-3<18:4n-3<20:5n-3≈22:6n-3) evidently contradicts the above postulate.…”
Section: Discussionsupporting
confidence: 86%
“…However, experimental tests are still rare and did not necessarily support this essential assumption [6][8]. Moreover, FA δ 13 C values of zooplankton and fish were not directly related to those of particulate organic matter in a marine field study [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a compoundspecific level, seston FA d 13 C values ranged from 225.3% down to 238.2%. This high intermolecular variability (i.e., 13%) would corroborate the multiple origins of carbon in seston Bec et al 2011 (Jones and Grey 2011). In our oxbow lake, the important organic matter loading in the shallow sediments would probably provide methane to methane-oxidizing bacteria to produce depleted CO 2 , which could result in depleted phytoplankton d 13 C values.…”
Section: Discussionmentioning
confidence: 61%
“…In a previous experimental study, such a pollen-based microbial food web was shown to transfer pollen carbon and upgrade its quality to promote zooplankton growth, especially by adding some long-chain PUFA, such as eicosapentaenoic acid (20:5v3; Masclaux et al 2011). Trophic upgrading of food quality by microorganisms has been associated with increasing digestibility and essential lipid compound production (such as C20 and C22-PUFA; Bec et al 2006). Indeed, long-chain PUFA and especially 20:5v3 are key essential compounds for metazoans, and their dietary availability may strongly determine secondary production in aquatic ecosystems, as metazoans cannot synthesize them de novo (Arts et al 2001;Mü llerNavarra et al 2004).…”
Section: Discussionmentioning
confidence: 99%